Almejas en golfos norpatagónicos, Argentina: disponibilidad trófica para aves playeras migratorias - Musmeci, Luciana Raquel (2013)
Peninsula Valdes, Argentinian Patagonia, is an area used as a trophic stopover by several shorebird species. These shorebirds are characterized by made long migrations and their survival depend for the sites where they stopover to forage. Diet studies indicate that the clams Darina solenoides and Tellina petitiana are key prey in their trophic ecology in Peninsula Valdes, preferring to ingest corporal sizes clams between 3 and 18 mm in length. The objective of this study there was to estimate population parameters (space distribution, density and age-structure) for both species of clams in order to evaluate them as trophic resource for shorebirds. Benthic samples were taken from a grid covering the intertidal area. In each square unit a sampling with 3 replicates at each sandy beach was carried out: Fracasso and Blancas beaches (were located in San Jose Gulf) and Colombo beach (in Nuevo Gulf). Each sample was collected with a core, sieved in situ and conserved for later analysis in the laboratory where both clam species were identified, quantified and measured taking the maximum anteroposterior lengths. Comparing the abundances of clams registered in this study with other stopover sites, these abundances of the intertidal clams of Peninsula Valdes would be sufficient to support the registered shorebirds abundances. Fracasso beach was the site with more suitable clams with preferable corporal sizes for shorebirds followed by Blancas beach.